Clinical Impact of Endoscopic Submucosal Dissection for Gastric Neuroendocrine Tumors: A Retrospective Study from Mainland of China - Wei-Feng Chen; Ping-Hong Zhou; Quan-Lin Li; Mei-Dong Xu; Li-Qing Yao (The Scientific World Journal)
As a minimally invasive technique, endoscopic resection may benefit patients diagnosed with early stage gastrointestinal neuroendocrine tumors (NETs). However, no studies have yet been published in which endoscopic submucosal dissection (ESD) has been applied for gastric NETs. For the first time a research group in China applied ESD to remove gastric NETs, and indicated that ESD should be considered for treatment of eligible gastric NETs because the technique shows a high histologically complete resection rate, provides accurate histopathological evaluation, has a low complication rate, and can be performed within a reasonable timeframe.